Design of Stimulation Device of Biological Active Points using 555 Timer - Gafarov, G.A.; Valehov, S.E. (Herald of Azerbaijan Engineering Academy, 2021)
Biologically active points as a method of non-traditional medical procedures and diagnostics, as well as being used for therapeutic purposes. Although this method has become the subject of mass research, a complete theory of the method has not yet been formed. The initial problem is related to the mechanism of action of biologically active points. Based on research, we can say that there are two approaches to explaining the mechanism of action. One is based on Chinese philosophy and the other on Western thought. One of the unexplored areas of biologically active points research is its application as a diagnostic tool. Biological structures are electrostimulated for therapeutic purposes. Stimulation can be performed through signals of different shapes and different parameters. However, if we are talking about the correct and effective stimulus, then the form and parameters of the stimulation signal must be clearly defined One of the most promising and new treatment methods of modern electrostimulation is treatment with rhythmic (pulsed, trapezoidal, exponential) currents. The indicators of such rhythmic currents should be determined to correspond to the physiological rhythm of the working biological system. The article discusses the design of a pulse device in the 555 digital timer to excite BAPs. Strong pulses are obtained due to the stability of the chip, so it is recommended to use it in the design of the device to influence BAPs.